Prevalence of uveitis in syphilis patients in Taiwan - Chia-Yun Chen; Hou-Ting Kuo; Alan Y. Hsu; Chun-Ju Lin; Ning-Yi Hsia; Peng-Tai Tien; Chun-Ting Lai; Huan-Sheng Chen; Yi-Yu Tsai (Emerging Microbes and Infections)
Few population-based studies have looked at the risk of uveitis among syphilis patients. Our study addresses the knowledge gap by reporting on uveitis risk in syphilis patients through a retrospective cohort study. The Taiwan National Health Insurance database was used for this study, covering the period from January 1st, 2009, to December 31st, 2020. We created a 1:4 propensity score matched cohort between the syphilis patients and controls, which accounted for gender, age, and comorbidities. The primary endpoint was the incidence of newly recorded uveitis. The assessment of uveitis risk in syphilis patients included the use of the Kaplan-Meier method and multivariate Cox proportional hazard model. A total of 31,597 syphilis patients and 126,379 matched comparisons were recruited. The uveitis incidence rate from our syphilis patients was 1.25 per 1000 person-years. The uveitis incidence rate from our non-syphilis group was 0.8 per 1000 person-years. After matching, the syphilis group was found to have a higher risk of developing uveitis (adjusted hazard ratio (aHR) [95% CI]: 1.57 [1.36–1.81], P < .001). Among males and individuals aged 20–34 years, subgroup analysis showed an increased risk of uveitis in the presence of syphilis infection. The Kaplan-Meier survival curve showed a significant difference in uveitis incidence between syphilis and non-syphilis groups (log-rank test P < .001). In summary, our study revealed that Taiwanese syphilis patients were at a higher risk of developing uveitis. These results highlight the need for regular ocular monitoring and screening in individuals with syphilis.